Static series-connected compensator with load-side connected shunt converter based on single-phase VSI for voltage sag mitigation - Srirattanawichaikul W. (2017)
© 2016 IEEE. This paper presents an improvement of the voltage restoration from voltage sags using the static series power quality compensator based on load-side connected shunt converter. The proposed topology is divided in two portions, which consists of the series and shunt configurations. The series converter is connected to the supply-side based on separated three sets single-phase voltage source inverters. The shunt converter uses a three-phase diode rectifier, which maintains the energy for the injection voltages with the dc-link capacitor. The algorithm technique of voltage sag detection and control method for compensation is based on the synchronously phase detection and the rotating reference frame transformation, which are independently controlled in each phase voltage. The performance of the proposed topology from the laboratory prototype is verified through experimental results.